Answer:
1. 4 , 3 , 7 , 3 , 0 , 3 , -2 , -1 , 6 , -7
2.
The equation = +2 - 4 + 7
The equation = -7 - 3 + 5
The equation = +6 - 9 + 4
The equation = +4 - 6 + 1
The equation = -5 - 2 + 9
The equation = 0 - 5 + 3
The equation = -3 - 1 + 4
The equation = -8 - 2 + 6
The equation = 0 - 8 + 2
The equation = +9 - 7 + 8
Explanation:
* Lets explain how to solve the problem
- If you have a starting point and move steps backward and move
steps forward, then to find your final position you will use this
equation:
The final position = start position - backward steps + forward steps
* Lets solve the questions
1.
∵ The starting position +3
∵ The backward steps 4
∴ The forward steps 5
∴ The final position = 3 - 4 + 5 = 4
∵ The starting position +7
∵ The backward steps 6
∴ The forward steps 2
∴ The final position = 7 - 6 + 2 = 3
∵ The starting position +5
∵ The backward steps 2
∴ The forward steps 4
∴ The final position = 5 - 2 + 4 = 7
∵ The starting position 0
∵ The backward steps 5
∴ The forward steps 8
∴ The final position = 0 - 5 + 8 = 3
∵ The starting position -4
∵ The backward steps 3
∴ The forward steps 7
∴ The final position = -4 - 3 + 7 = 0
∵ The starting position +1
∵ The backward steps 7
∴ The forward steps 9
∴ The final position = 1 - 7 + 9 = 3
∵ The starting position -6
∵ The backward steps 1
∴ The forward steps 5
∴ The final position = -6 - 1 + 5 = -2
∵ The starting position -2
∵ The backward steps 5
∴ The forward steps 6
∴ The final position = -2 - 5 + 6 = -1
∵ The starting position 8
∵ The backward steps 3
∴ The forward steps 1
∴ The final position = 8 - 3 + 1 = 6
∵ The starting position -9
∵ The backward steps 2
∴ The forward steps 4
∴ The final position = -9 - 2 + 4 = -7
2.
- The equation which represent the movement is:
start position - backward steps + forward steps
∵ The starting position +2
∵ The backward steps 4
∴ The forward steps 7
∴ The equation = +2 - 4 + 7
∵ The starting position -7
∵ The backward steps 3
∴ The forward steps 5
∴ The equation = -7 - 3 + 5
∵ The starting position +6
∵ The backward steps 9
∴ The forward steps 4
∴ The equation = +6 - 9 + 4
∵ The starting position +4
∵ The backward steps 6
∴ The forward steps 1
∴ The equation = +4 - 6 + 1
∵ The starting position -5
∵ The backward steps 2
∴ The forward steps 9
∴ The equation = -5 - 2 + 9
∵ The starting position 0
∵ The backward steps 5
∴ The forward steps 3
∴ The equation = 0 - 5 + 3
∵ The starting position -3
∵ The backward steps 1
∴ The forward steps 4
∴ The equation = -3 - 1 + 4
∵ The starting position -8
∵ The backward steps 2
∴ The forward steps 6
∴ The equation = -8 - 2 + 6
∵ The starting position 0
∵ The backward steps 8
∴ The forward steps 2
∴ The equation = 0 - 8 + 2
∵ The starting position +9
∵ The backward steps 7
∴ The forward steps 8
∴ The equation = +9 - 7 + 8